Comparative genomics of Rhizophagus irregularis, R. cerebriforme, R. diaphanus and Gigaspora rosea highlights specific genetic features in Glomeromycotina. Issue 3 (25th February 2019) - Morin, Emmanuelle; Miyauchi, Shingo; San Clemente, Hélène; Chen, Eric C. H.; Pelin, Adrian; de la Providencia, Ivan; Ndikumana, Steve; Beaudet, Denis; Hainaut, Mathieu; Drula, Elodie; Kuo, Alan; Tang, Nianwu; et al.
Summary: Glomeromycotina is a lineage of early diverging fungi that establish arbuscular mycorrhizal (AM) symbiosis with land plants. Despite their major ecological role, the genetic basis of their obligate mutualism remains largely unknown, hindering our understanding of their evolution and biology. We compared the genomes of Glomerales ( Rhizophagus irregularis, Rhizophagus diaphanus, Rhizophagus cerebriforme ) and Diversisporales ( Gigaspora rosea ) species, together with those of saprotrophic Mucoromycota, to identify gene families and processes associated with these lineages and to understand the molecular underpinning of their symbiotic lifestyle. Genomic features in Glomeromycotina appear to be very similar with a very high content in transposons and protein‐coding genes, extensive duplications of protein kinase genes, and loss of genes coding for lignocellulose degradation, thiamin biosynthesis and cytosolic fatty acid synthase. Most symbiosis‐related genes in R. irregularis and G. rosea are specific to Glomeromycotina. We also confirmed that the present species have a homokaryotic genome organisation. The high interspecific diversity of Glomeromycotina gene repertoires, affecting all known protein domains, as well as symbiosis‐related orphan genes, may explain the known adaptation of Glomeromycotina to a wide range of environmental settings. Our findings contribute to an increasingly detailed portrait of genomic features defining the biology of AM fungi.